Synthesis of silver modified bioactive glassy materials with antibacterial properties via facile and low-temperature route - Gonzalo-Juan, Isabel; Xie, Fangtong; Becker, Malin; Tulyaganov, Dilshat; Ionescu, Emanuel; Lauterbach, Stefan; De Angelis Rigotti, Francesca; Fischer, Andreas; Riedel, Ralf (Materials, 2020)
There is an increasing clinical need to develop novel biomaterials that combine regenerative and biocidal properties. In this work, we present the preparation of silver/silica-based glassy bioactive (ABG) compositions via a facile, fast (20 h), and low temperature (80 °C) approach and their characterization. The fabrication process included the synthesis of the bioactive glass (BG) particles followed by the surface modification of the bioactive glass with silver nanoparticles. The microstructural features of ABG samples before and after exposure to simulated body fluid (SBF), as well as their ion release behavior during SBF test were evaluated using infrared spectrometry (FTIR), ultraviolet-visible (UV-Vis) spectroscopy, X-ray diffraction (XRD), electron microscopies (TEM and SEM) and optical emission spectroscopy (OES). The antibacterial properties of the experimental compositions were tested against Escherichia coli (E. coli). The results indicated that the prepared ABG materials possess antibacterial activity against E. coli, which is directly correlated with the glass surface modification.
Gesehen am 20.01.2021